Analisis Likuiditas, Solvabilitas, dan Profitabilitas Terhadap Kinerja Keuangan Perusahaan Bank Central Asia (BCA) Periode 2017-2021 - Fazdhil Muhammad Rafael; Gita Genia Fatihat (Cakrawala Repositori IMWI, 2023)
There are several ratios that can affect the financial performance of a company. These factors are often used as a reference by investors or companies in making investment decisions, including Liquidity, Solvency, and Profitability Ratios. The purpose of this study is to determine the relationship between these three ratios and the financial performance of PT Bank Central Asia for the period 2017-2021. The data used in this study used data from the Annual Report of PT Bank Central Asia for the 2017-2021 period. The results showed that there was a relationship between the Profitability variable and the Financial Performance of PT Bank Central Asia for the 2017-2021 period.